Disturbed Serotonergic Neurotransmission and Oxidative Stress in Elderly Patients with Delirium - Angelique Egberts (Dementia and Geriatric Cognitive Disorders Extra, 2015)
Background: Oxidative stress and disturbances in serotonergic and dopaminergic neurotransmission may play a role in the pathophysiology of delirium. Aims: In this study, we investigated levels of amino acids, amino acid ratios and levels of homovanillic acid (HVA) as indicators for oxidative stress and disturbances in neurotransmission. Methods: Plasma levels of amino acids, amino acid ratios and HVA were determined in acutely ill patients aged ≥65 years admitted to the wards of Internal Medicine and Geriatrics of the Erasmus University Medical Center and the ward of Geriatrics of the Havenziekenhuis, Rotterdam, The Netherlands. Differences in the biochemical parameters between patients with and without delirium were investigated by analysis of variance in models adjusted for age, gender and comorbidities. Results: Of the 86 patients included, 23 had delirium. In adjusted models, higher mean phenylalanine/tyrosine ratios (1.34 vs. 1.14, p = 0.028), lower mean tryptophan/large neutral amino acids ratios (4.90 vs. 6.12, p = 0.021) and lower mean arginine levels (34.8 vs. 45.2 µmol/l, p = 0.022) were found in patients with delirium when compared to those without. No differences were found in HVA levels between patients with and without delirium. Conclusion: The findings of this study suggest disturbed serotonergic neurotransmission and an increased status of oxidative stress in patients with delirium.